171k views
4 votes
Cual es la función inversa de: f(x)=x2-3

User Jperelli
by
4.5k points

2 Answers

4 votes

Answer:

f−1(x)=√x−3,−√x−3

User Asanka
by
5.9k points
1 vote

Find the inverse function f(x)=x^2-3.

Replace f(x) with y.

y = x²-3

Swap the variables.

x = y²-3

Solve for y.

Rewrite the equation as y² - 3x = x.

Add 3 to both sides of the equation.

y² = x - 3

Take the square root on both sides of the equation to eliminate the exponent on the left side.


\bf{y=\pm√(x+3) }

The complete solution is the result of the positive or negative portions of the solution.

First, use the positive value of ± to find the first solution.


\bf{y=√(x+3) }

Then use the negative value of ± to find the second solution.


\bf{y=-√(x+3) }

The complete solution is the result of the positive or negative portions of the solution.


\bf{y=√(x+3) }


\bf{y=-√(x+3) }

Solve for y and substitute with
\bf{f^(-1)(x) }.

substitute f⁻¹( x ) for y to show the final answer.


\boldsymbol{f^(-1)(x)=√(x+3),-√(x+3) }

Set the composite results function.


\boldsymbol{g(f(x)) }

Evaluate g(f(x)) by substituting the value of f into g.


\boldsymbol{\sqrt{(x^(2) -3)+3 } }

Add −3 and 3.


\boldsymbol{g(x^(2) -3)=\sqrt{x^(2) +0} }

Add and 0.


\boldsymbol{g(x^(2) -3)=\sqrt{x^(2)} }

Extract terms from under the radical, assuming positive real numbers.


\boldsymbol{g(x^(2) -3)=x }

Given the
\bf{g(f(x))=x,f^(-1)(x)=√(x+3),-√(x+3) } is the inverse of
\bf{f(x)=x^(2) -3. }


\boldsymbol{f^(-1)(x)=√(x+3),-√(x+3). }

User Chimmi
by
5.5k points